2020
DOI: 10.1063/5.0013919
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microfluidic processing on the viability of boar and bull spermatozoa

Abstract: The use of microfluidics in artificial reproductive technologies for manipulation or assessment of spermatozoa is unique in the sense that it is not always an end point measurement and the sample may be used afterward. During microfluidic processing, spermatozoa are exposed to shear stress, which may harm viability and functioning of spermatozoa. The shear stresses during general microfluidic processing steps were calculated and compared to estimated shear stresses during ejaculation. The viability of boar and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Similar results were observed by Gode et al (2019) and Parrella et al (2019), when comparing microfilters versus density gradient centrifugation, as progressive motility was greater than 96% versus 64 to 91%, respectively. However, Hamacher et al (2020) showed that the quality of microfluidics processed bull spermatozoa did not differ significantly from that processed by conventional methods. Furthermore, Lee et al (2009) reported that the most efficient technique for removing spermatozoa with damaged membranes is using glass wool filtration.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed by Gode et al (2019) and Parrella et al (2019), when comparing microfilters versus density gradient centrifugation, as progressive motility was greater than 96% versus 64 to 91%, respectively. However, Hamacher et al (2020) showed that the quality of microfluidics processed bull spermatozoa did not differ significantly from that processed by conventional methods. Furthermore, Lee et al (2009) reported that the most efficient technique for removing spermatozoa with damaged membranes is using glass wool filtration.…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that MF yielded similar results to DGC and was superior to results from SU, but no clinical outcomes were investigated [ 128 ]. Yet, despite the widely reported benefits of MF sorting, it has also been demonstrated that some microfluidics may impose stress upon boar, but not bull, spermatozoa and negatively impact viability [ 135 ]. As boar spermatozoa are often used as a model for human spermatozoa, this phenomenon, as well as potential injuries to spermatozoa from other species, requires further investigation.…”
Section: Sorting Semen: Significance and Methodsmentioning
confidence: 99%
“…Moreover, it has been shown that the effect of microfluidic processing, including PFF, on the spermatozoa viability is low. 36 The used chip dimensions and flow rates used in the viability study 36 were similar and in the same range as the ones used in this study. There were differences in our proposed separation technique and the previously proposed one by Berendsen et al, which can cause the difference in spermatozoa recovery such as the chip design, flow rate ratio and sample composition.…”
Section: Lab On a Chip Accepted Manuscriptmentioning
confidence: 99%
“…Besides that, PFF does not seem to be harmful to the cells, since we have previously shown that the effect of PFF on the viability of boar and bull spermatozoa, is less than or similar to the current used processing techniques such as centrifugation and flow cytometry. 36 To our knowledge, for the first time a microfluidic device is presented that can efficiently separate viruses from porcine spermatozoa to decrease the virus load prior AI. As a virus model cowpea chlorotic mottle viruses (CCMVs) were used, which have a similar size (28 nm) to typical viruses found in semen.…”
Section: Introductionmentioning
confidence: 99%